The Role of Fathers in the Formation of Emotion Regulation in Adolescent Girls: A Parenting Review - Mirza, Rina; Martha Sipayung, Eunike; Salli Salsabila, Aghnia; Berliana br Silalahi, Rut; Marpaung, Winida (Program Studi Psikologi, Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Mulawarman, 2025)
Father involvement in parenting plays a crucial role in influencing adolescent emotion regulation, which is a key factor in children's psychological development. The aim of this study is to examine the relationship between paternal involvement and emotional regulation in female adolescents at SMKN 6 Medan. The research used a quantitative approach with a correlational design. The sample consisted of 231 female students from grades X, XI, and XII, selected randomly. Data were collected using questionnaires on emotional regulation and paternal involvement, and analyzed using Pearson correlation techniques. The results showed a significant positive correlation between paternal involvement and emotional regulation in female adolescents (r = 0.440, p < 0.05). The higher the paternal involvement, the better the students' ability to manage their emotions. The implications of this research suggest that paternal involvement plays a crucial role in adolescents' emotional development, and programs that encourage paternal involvement in parenting and education are expected to enhance adolescents' emotional regulation, preparing them to better face life's challenges.Keterlibatan ayah dalam pengasuhan memiliki peran penting dalam mempengaruhi regulasi emosi remaja, yang menjadi faktor krusial dalam perkembangan psikologis anak. Tujuan penelitian ini adalah untuk mengetahui hubungan antara keterlibatan ayah dan regulasi emosi pada remaja perempuan di SMKN 6 Medan. Metode yang digunakan adalah pendekatan kuantitatif dengan desain korelasional. Sampel penelitian ini terdiri dari 231 siswi kelas X, XI, dan XII yang dipilih secara acak. Data dikumpulkan menggunakan kuesioner tentang regulasi emosi dan keterlibatan ayah, serta dianalisis dengan teknik korelasi Pearson. Hasil penelitian menunjukkan bahwa terdapat hubungan positif yang signifikan antara keterlibatan ayah dan regulasi emosi pada remaja perempuan (r = 0.440, p < 0.05). Semakin tinggi keterlibatan ayah, semakin tinggi kemampuan siswi dalam mengelola emosi mereka. Implikasi penelitian ini menunjukkan bahwa keterlibatan ayah berperan penting dalam perkembangan emosional remaja, dan program yang mendorong keterlibatan ayah dalam pengasuhan dan pendidikan anak diharapkan dapat meningkatkan regulasi emosi remaja, mempersiapkan mereka untuk menghadapi tantangan hidup dengan lebih baik.